Comparative Study of the Cultural Connotations of Proverbs with Zoonyms in Chinese and Spanish - Lu, Geng (Sinología hispánica. China Studies Review, 2024)
In contact with human beings, people attach different cultural meanings to animals according to their figurative characteristics, character traits and different influences on human society. Many Chinese and Spanish proverbs contain images of animals, and these proverbs are vividly reflected in mythology, literature and everyday communication. However, some sayings with zoonyms have different symbolic meanings in different cultural contexts. This article takes proverbs with zoonyms an example, and then reveals the reasons for the meaning differences of proverbs with zoonyms in Chinese and Spanish from different perspectives, as well as a comparative analysis of the deeper cultural meanings of proverbs with zoonyms in the two languages, in order to effectively deepen cultural understanding.